Study of the Effects of Epinephrine on Cerebral Oxygenation and Metabolism During Cardiac Arrest and Resuscitation by Hyperspectral Near-Infrared Spectroscopy. Issue 4 (April 2019) - Nosrati, Reyhaneh; Lin, Steve; Mohindra, Rohit; Ramadeen, Andrew; Toronov, Vladislav; Dorian, Paul
Abstract : Objectives: Epinephrine is routinely administered to sudden cardiac arrest patients during resuscitation, but the neurologic effects on patients treated with epinephrine are not well understood. This study aims to assess the cerebral oxygenation and metabolism during ventricular fibrillation cardiac arrest, cardiopulmonary resuscitation, and epinephrine administration. Design: To investigate the effects of equal dosages of IV epinephrine administrated following sudden cardiac arrest as a continuous infusion or successive boluses during cardiopulmonary resuscitation, we monitored cerebral oxygenation and metabolism using hyperspectral near-infrared spectroscopy. Settings: A randomized laboratory animal study. Subjects: Nine healthy pigs. Interventions: None. Measurements and Main Results: Our study showed that although continuous epinephrine administration had no significant impact on overall cerebral hemodynamics, epinephrine boluses transiently improved cerebral oxygenation (oxygenated hemoglobin) and metabolism (cytochrome c oxidase) by 15% ± 6.7% and 49% ± 18%, respectively ( p < 0.05) compared with the baseline (untreated) ventricular fibrillation. Our results suggest that the effects of epinephrine diminish with successive boluses as the impact of the third bolus on brain oxygen metabolism was 24.6% ± 3.8% less than that of the first two boluses. Conclusions: Epinephrine administration by bolus resulted in transient improvements in cerebral oxygenation and metabolism, whereas continuous epinephrine infusion did not, compared with placebo. Future studies are needed to evaluate and optimize the use of epinephrine in cardiac arrest resuscitation, particularly the dose, timing, and mode of administration. Abstract : Supplemental Digital Content is available in the text.